Occurrence, molecular diversity and pathogenicity of Acanthamoeba spp. isolated from aquatic environments of Northeastern Brazil. - Matos de Oliveira, Yrna Lorena; Lima, Erica Tirzah Santos; Rott, Marilise Brittes; Fernandes, Roberta Pereira Miranda; Jain, Sona; de Aragão Batista, Marcus Vinicius; Santana Dolabella, Silvio (International Journal of Environmental Health Research, 2023)
Acanthamoeba is a free-living amoeba (FLA) that is ubiquitous in nature and can cause serious pathologies in humans. This protozoan has been detected in several environmental sources, such as soil, water, and swimming pools. The aim of this study was to evaluate the occurrence and molecular diversity of Acanthamoeba spp. in aquatic environments of the state of Sergipe, northeastern Brazil, and to determine the pathogenic potential of the isolated samples. A total of 138 samples were collected from 69 aquatic environments and, after cell culture, 74% of the samples were positive for FLA, 47% belonging to the genus Acanthamoeba. Genotypic analysis was performed using the primers JDP1 and JDP2, confirming distinct Acanthamoeba genotypes: 18 (75%) isolates belonging to genotype T4, two (8%) to T3, and one isolate (4%) to genotype T5. Tests carried out to analyze the pathogenic potential showed that 11 isolates could grow at 0.5 M mannitol concentration and seven isolates supported hyperosmolarity. In the thermotolerance test, two isolates grew at 37°C. These results confirm the presence and the pathogenic potential of FLA of the genus Acanthamoeba in aquatic environments of the municipalities of Sergipe.